Production risk and technical efficiency of fish farms in Ghana - Onumah, E.E.; Onumah, J.A.; Onumah, G.E. (Elsevier B.V., 2018)
This paper adopts the stochastic frontier model with flexible risk to analyze production risk, technical efficiency and its determinants of fish farms in four regions of Ghana including Greater Accra, Volta, Western and Ashanti regions. The study employs a two year panel data from 320 farms making a total of 640 observation through a random selection. The findings demonstrates that the translog model is best fit for the mean output function, whilst the input variables: hired labour, family labour, fingerlings, feed and other cost are identified to positively influence fish farm output at an increasing returns to scale. The paper also finds that feed and other cost are risk increasing inputs, whilst hired labour, family labour and fingerlings are identified to be risk decreasing inputs. The estimated average technical efficiency score of 0.74 shows that efficiency is compromised when the production technology is modeled without the flexible risk property which gave a score of 0.87. Additionally, the results show that age2, experience, pond area, gender, pond type and fish farming education significantly influence technical efficiency of farmers. This paper also highlights that technical efficiency of fish farms in the study area improved over time. In conclusion, the paper notes that on the average, 26% of potential output is lost due to technical inefficiency and production risk and given the present state of technology and input level, the possibility of enhancing production can be achieved by reducing technical inefficiency by 26% through adoption of practices of the best fish farm, whilst taking production risk into consideration. © 2018
Keywords: Efficiency determinants; Flexible risk property; Panel data; Productivity; Stochastic frontier model